问题 解答题
计算
(1)(2x-y)(4x2-y2)(2x+y)
(2)-2(
1
3
x-
3
2
y)2
(3)(x-3y)(x-
1
2
y)
(4)(-
1
5
a3x4-
9
10
a2x3)÷(-
3
5
ax2
(5)x2-(x+2)(x-2)-(x+2)2
(6)(2x2+x)-[4x2-(3x2-x)]
答案

(1)(2x-y)(4x2-y2)(2x+y),

=(4x2-y22

=16x4-8x2y2+y4

(2)-2(

1
3
x-
3
2
y)2

=-2(

1
9
x2-xy+
9
4
y2),

=-

2
9
x2+2xy-
9
2
y2

(3)(x-3y)(x-

1
2
y)=x2-
7
2
xy+
3
2
y2

(4)(-

1
5
a3x4-
9
10
a2x3)÷(-
3
5
ax2)=
1
3
a2x2+
3
2
ax;

(5)x2-(x+2)(x-2)-(x+2)2

=x2-(x2-4)-(x2+4x+4),

=-x2-4x;

(6)(2x2+x)-[4x2-(3x2-x)],

=2x2+x-4x2+3x2-x,

=x2

单项选择题
单项选择题